ON THE ECOBIOLOGICAL FEATURES OF VELACHERY LAKE ON A LUNAR ECLIPSE DAY - RAMARANI, S; RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The effect of lunar eclipse on ecobiological features of Velachery lake, Chennai, was studied on 16th July 2000. The zooplankton species count revealed the dominance of Mesocyclops sp. among the identified forms.